[Close-Up of "Sheep Flower" and Ring Near Askja] - Streng, Evelyn Fiedler (1975)
Photograph of a "sheep flower" and a ring near Askja. The small, white flowers sit on a shiny, green stems along grey rocks. The grey rocks dot along black dirt throughout the photograph. A silver river sits to the left of the flowers.